Preparation of honokiol-loaded titanium dioxide nanotube drug delivery system and its effect on CAL-27 cells - Tang, Kaiqi; Su, Han; Qu, Zhi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Tongue cancer is the most common type of oral cancer, and patients have a poor prognosis and quality of life after conventional surgical treatment.Honokiol (HNK) is a kind of lignan extracted from Chinese herbal medicine Houpu, many domestic and international experiments have demonstrated its anti-tumor effect.Titanium dioxide nanotube (TNTs) is a kind of nanomaterial which can be used as drug carrier. The purpose of this study is to explore the effects of HNK-loaded TNTs delivery system (HNK-TNTs) on anti-tumor.TNTs were prepared by anodic oxidation method, and HNK was loaded onto TNTs by physical adsorption. The effect of HNK-TNTs on the proliferation, migration and apoptosis of CAL-27 cells were explored by CCK-8 experiment, scratch assay, live and dead staining and cellular immunofluorescence analysis.The material characterization test results showed that we had successfully prepared HNK-TNTs. CCK-8 experiment, scratch assay showed that the proliferation and migration ability of CAL-27 cells were significantly weakened after treatment with HNK-TNTs, and their cell proliferation rates significantly decreased. Live/dead staining, cell immunofluorescence analysis showed that HNK-TNTs could promote CAL-27 cells apoptosis by increasing the expression levels of the apoptosis-related protein Bax and Fas.In this experiment, we had successfully prepared Honokiol-loaded titanium dioxide nanotube drug delivery system (HNK-TNTs) and compared the effects of single drug HNK and HNK-TNTs on the proliferation, apoptosis and migration of tongue cancer CAL-27 cells. This experiment showed that HNK-TNTs had greater anti-proliferative, apoptosis-promoting and migration-inhibiting effects than the HNK as a single drug.